Novel insights into delayed bitterness control in traditional Huangjiu: Regulating bacterial community by inoculated with Saccharomyces cerevisiae SC-6 - Haiyan Yu; Shiqi Wu; Qiaowei Li; Chen Chen; Qian Chen; Huaixiang Tian (Food Chemistry: X)
Under semi-open brewing conditions, traditional Huangjiu often suffers from unstable flavor quality, including occasional delayed bitterness. To address this issue, a yeast strain, Saccharomyces cerevisiae SC-6, was screened for its ability to reduce delayed bitterness. The effects of SC-6 on the flavor and microbial composition of Huangjiu exhibiting high levels of delayed bitterness were also investigated. GC–MS analysis indicated that S. cerevisiae SC-6 significantly lowered the levels of key delayed bitter compounds, including octanoic acid, ethyl caprylate, benzaldehyde, and phenol, by 54.80 %, 12.21 %, 31.38 %, and 43.23 %, respectively. PCoA analysis demonstrated that SC-6 altered the microbial community of traditional Huangjiu. Correlation analysis indicated that reduced bitter compounds correlated with changed abundances of Rhodopseudomonas, unclassified_f_Micromonosporaceae, Lachnoclostridium, Lactobacillus, Streptomyces, Clostridium_sensu_stricto_1, Staphylococcus, Pseudomonas, unclassified_o__Enterobacterales, and Candida. These results provide effective guidance for controlling off-flavors in traditional Huangjiu and clarify the role of microorganisms in the production of bitter substances.